If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 6 = 3x + -9 Reorder the terms: 6 + -5x = 3x + -9 Reorder the terms: 6 + -5x = -9 + 3x Solving 6 + -5x = -9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + -5x + -3x = -9 + 3x + -3x Combine like terms: -5x + -3x = -8x 6 + -8x = -9 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + -8x = -9 + 0 6 + -8x = -9 Add '-6' to each side of the equation. 6 + -6 + -8x = -9 + -6 Combine like terms: 6 + -6 = 0 0 + -8x = -9 + -6 -8x = -9 + -6 Combine like terms: -9 + -6 = -15 -8x = -15 Divide each side by '-8'. x = 1.875 Simplifying x = 1.875
| log(12x+2)=log(2x-1)+1 | | 16xy+x^2+64y^2=0 | | 4+1f=17 | | 4k-12-6k=2k-6+6k+2 | | ln(2-1)=0 | | 4k-12-6=2k-6+6k+2 | | x^3-4x^2+6x=0 | | 8-3d=12 | | 432=-16t^2+64t+512 | | 2x^5-3x^4-2x^3+7x^2-2x-6=0 | | c^2-16h^4=0 | | 6r+3-2t+4=5 | | cosh(x)*cos(x)=1 | | 90=60+t | | -3b+23=80 | | 90=60t | | 2(k-4)=5k+2 | | x-4x-3=0 | | 2(k-4)=5k-2 | | 17x+7x=14-36 | | -4x-1+6x+4= | | 8(r-5)(r+5)=0 | | -4x+2+7x+3= | | 9x+4x-8x=8+7 | | 2(x-3)=(2x+5) | | 6y+2(3+6.5y)=2.5+15.5y | | 3+1b=5 | | 11p-9+8p-7+14=12p+9p+4 | | 8x-24y=144 | | 0.5r+5.2=2.8 | | 7(24-x)=5x | | 4x^2-2ax-2bx+ab=0 |